EFEKTIVITAS SENAM HAMIL PADA IBU TRIMESTER III TERHADAP JENIS PERSALINAN: The Effectiveness of Pregnancy Exercises in the Thirth Trimester on the Type of Labor - Ni’mah Mufidah; Rantiningsih Sumarni; Hidayah Nurhayati; NI'MAH MUFIDAH (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
One of the causes of the high number of maternal deaths is prolonged labor. The form of prevention of prolonged labor that can be done is by controlling the five factors of the birth process which include power, passage, passenger psychology and helpers. Power is a very important birth factor, originating from pregnant women which can be controlled with pregnancy exercises. This research aim is to determine the outcomes of maternal exercise in the third trimester during the birth process. This research method is retrospective, with a total sampling technique of 25 and data analysis use Chi Square. The results of this study were that the majority of pregnant women in the third trimester did regular pregnancy exercise, with as 20 respondents (80.0%). Pregnant women in the third trimester who do pregnancy exercises regularly mostly have a normal delivery process, 17 respondents (85%), and the Pearson Chi-Square Test shows that the significant value is p value = 0.035 < a (0.05), so H1 is accepted. Keywords: Labor Process; Pregnancy Exercise Outcomes; Third Trimester